The Effectiveness of Hitting Zone Exercises in Softball Sports - Dikdik Fauzi Dermawan; Tedi Purbangkara (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effectiveness of hitting zone training on the results of hitting on softball. Subjects consisted of 10 right hitters and 5 left hitters ranging in age from 19 to 23 who were members of regional training. Subjects were given a hitting zone training model. Before being given the hitting zone training model, all subjects were subjected to a preliminary test to determine their ability to hit a softball with machine pitching, then the subjects were given the hitting zone training model after having carried out the hitting zone training model for 16 meetings. Subjects were retested as a final test of their softball hitting skills. . Test the effectiveness using the productivity of hitting a softball. Data analysis using SPSS 21. The results of the research on the effectiveness test using the t-test obtained a t-test of 12.458 with a significance level of using t-table 0.05 of 2.145. Based on the calculation results obtained t-test = 12.458> t table 0.05 = 2.145 means that the developed model provides effectiveness in hitting softball balls. Based on the research results, it can be concluded that the hitting zone training model gives effectiveness to the results of the softball strokes.